Exogenous GM-CSF therapy for autoimmune pulmonary alveolar proteinosis: a systematic literature review - Wushu Chen; Wushu Chen; Xin Feng; Lun-kai Yao; Xingpei Li; Zhen-ming Yang; Xiu-yu Qin; Yu Li; Ye Qiu (Frontiers in Medicine)
BackgroundGranulocyte-macrophage colony-stimulating factor (GM-CSF) therapy is an important treatment for autoimmune pulmonary alveolar proteinosis (aPAP). Exogenous GM-CSF treatment can be administered either through subcutaneous injection or nebulized inhalation. However, data on the effectiveness and safety of these two approaches are lacking.MethodWe conducted a systematic literature review of different methods, including subcutaneous injection and nebulized inhalation of GM-CSF, for the treatment of aPAP patients. Patients were divided into a subcutaneous injection group (SIG) and a nebulized inhalation group (NIG) according to the route of administration. Treatment efficacy and safety, including adverse events, were statistically assessed. We analyzed different GM-CSF treatment cycles with different time intervals. The analyses were performed using chi-square tests, unpaired t-tests, and Kruskal–Wallis H-tests.ResultsA total of 304 aPAP patients were treated with GM-CSF, including 66 (21.7%) in the SIG and 238 (78.3%) in the NIG. In total, we identified 220 (72.37%) patients whose treatment was effective and 84 (27.63%) patients whose treatment was ineffective. Efficacy was achieved in 54.55% (36/66) of the SIG patients and 77.31% (184/238) of the NIG patients (P < 0.001). More metrics were changed than in the NIG than SIG, suggesting the superior effectiveness of nebulized inhalation. The nebulized inhalation of GM-CSF was more effective (P < 0.001) and caused fewer adverse events than its subcutaneous injection. A significant difference in the NIG was noted across treatment durations, with an efficacy rate of 88% for those treated for over 24 weeks, compared with 48% in the SIG (P < 0.001). Among the NIG patients, the optimal efficacy was found to be at a dosage of 300–400 μg/d, with diminishing efficacy at higher doses (P < 0.036).ConclusionNebulized inhalation is a more effective and safer route of GM-CSF administration than subcutaneous injection is, with a potential optimal dosage of 300–400 μg/day, and the duration of GM-CSF treatment via nebulized inhalation with the greatest efficacy is >24 weeks.